The effect of combined oral contraceptive and hormonal implant on plasma glucose level and liver function in women: A cross-sectional study - Abera, Wondwossen; Bizuayehu, Temesgen; Fikre, Rekiku; Jisso, Meskerem (Ethiopian Journal of Medical and Health Sciences, 2025)
Background: Long-term use of combined oral contraceptives and implant contraceptives was associatedwith some adverse metabolic effects, including effects on serum glucose, body weight, and liverenzymes. However, recent epidemiological reports suggest a possible increased risk of diabetes and liverdisease among users. This study aims to assess the effect of hormonal implants and combinedoral contraceptives use on glucose metabolism and liver function among women who attend familyplanning services.Methods: An institution-based comparative cross-sectional study was conducted to assess the effect ofhormonal implant contraceptives and combined oral contraceptives on glucose metabolism and liverfunction status among women of reproductive age from September 15- June 30, 2022. A total of 162women (86 hormonal implant users, 26 combined oral contraceptive users, and 50 non-users) wereincluded in the study. A one-way analysis of variance was used to examine differences in outcomes.Pearson correlation was used to identify the association between outcome variables and the duration ofimplant use.Results: The prevalence of diabetes among study participants in Leku General Hospital and YirbaPrimary Hospital of Sidama Region was 10.5% (95% CI: 6.2- 15.4%). The prevalence of diabetes was11.6% (95% CI: 5.8-18.6), 11.5% (95% CI: 0-26.9), and 8% (95% CI: 2.0-16.0) among implant users,combined oral contraceptives users and non-users, respectively. From Bonferroni's post-hoc analysis,implant users had a significantly higher mean hip-to-waist ratio than non-users (p=0.024). Implant usershad significantly higher mean systolic blood pressure (p = 0.027) than combined oral contraceptive users.Longer implant use was associated with lower ALT levels (p = 0.044 and r = -0.22).Conclusion: Longer implant use was associated with lower ALT levels and higher waist-to-hip ratio